1992
DOI: 10.1136/adc.67.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BCG vaccination at birth and at third month of life.

Abstract: Tuberculosis is an important health problem in developing countries and the BCG vaccine plays an important part in preventing the disease. There are different reports about the preventive value of BCG. Some of them claim that it is satisfactory while others suggest that it provides little protection. There are also varying ideas about the optimum time to vaccinate babies, some studies suggesting that late vaccination confers a high degree of protection. This prospective controlied study has been undertaken to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 8 publications
0
20
0
2
Order By: Relevance
“…Given that low progression or "resistance" to HIV infection is associated with preferential expression of Thl cytokines and that, conversely, progression of the disease is associated with dominant expression of Th2 cytokines, it is reasonable to speculate that the more rapid evolution of neonatal HIV infection is related to the early expression of IL-4 (2). The preventive value of BCG vaccination remains diversely appreciated (54), and it was reported recently that BCG given during the first 3 d of life is much less efficient and generates more complications than when given after 3 mo (55). These unpublished observations).…”
Section: Discussionmentioning
confidence: 93%
“…Given that low progression or "resistance" to HIV infection is associated with preferential expression of Thl cytokines and that, conversely, progression of the disease is associated with dominant expression of Th2 cytokines, it is reasonable to speculate that the more rapid evolution of neonatal HIV infection is related to the early expression of IL-4 (2). The preventive value of BCG vaccination remains diversely appreciated (54), and it was reported recently that BCG given during the first 3 d of life is much less efficient and generates more complications than when given after 3 mo (55). These unpublished observations).…”
Section: Discussionmentioning
confidence: 93%
“…Many animal models also support this theory (28)(29)(30)(31)(32)(33)(34)(35). However, previous studies that have delayed the BCG vaccine in human infants have found similar IFN-g responses to purified protein derivative (PPD), increased TST reactivity and increased polyfunctional T cells after in vitro stimulation with BCG vaccine (36)(37)(38)(39)(40), although BCG efficacy was not determined in these studies.…”
mentioning
confidence: 93%
“…It could account for the age-dependent clinical pattern of infectious diseases such as hepatitis, mononucleosis or toxoplasmosis in which symptoms are believed to be essentially immune mediated and which remain mostly asymptomatic in young children compared to adults. It would also explain the lower immunogenicity and higher frequency of complications following BCG immunization performed at birth rather than at a few months of age [11,16]. Finally, it could be linked to the preferential induction of allergic reactions upon early exposure to environmental antigens.…”
Section: Cd4 T Cell Responsesmentioning
confidence: 99%